1970
DOI: 10.1104/pp.45.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Oil Seeds

Abstract: The germination and ethylene production by dormant Virginia-type peanut seeds were observed in relation to phytohormone treatments that could conceivably release the dormancy of these seeds. A comparison was made between the effects of these treatments on the less dormant apical seeds and the more dormant basal seeds. Indole-3-acetic acid did not stimulate ethylene production by, or germination of, the dormant seeds to any extent. Gibberellic acid at 5 X 104 M stimulated ethylene production by apical seeds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

1971
1971
1999
1999

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
4
23
0
1
Order By: Relevance
“…It remains uncertain whether, as this hypothesis requires, the level of endogenously formed ethylene reaches a sufficient concentration at its site of action within the seeds to have a significant influence on germination. However, this seems probable in view of previous reports which suggest that ethylene is an essential prerequisite of germination in lettuce and other seeds (3,4,(6)(7)(8)11). …”
Section: Discussionmentioning
confidence: 41%
“…It remains uncertain whether, as this hypothesis requires, the level of endogenously formed ethylene reaches a sufficient concentration at its site of action within the seeds to have a significant influence on germination. However, this seems probable in view of previous reports which suggest that ethylene is an essential prerequisite of germination in lettuce and other seeds (3,4,(6)(7)(8)11). …”
Section: Discussionmentioning
confidence: 41%
“…Auxins (3) and gibberellic acid (10,17) are known to stimulate ethylene formation in plant tissues, but in our preliminary observation neither 5 x 1 0' M gibberellic acid nor 1 X 10"-M IAA accelerated germination of aged seeds. In this study, however, the exposure of aged seeds to the gas enhanced their germination and growth.…”
Section: Discussionmentioning
confidence: 82%
“…With (9); it also breaks the dormancy of seed of various species (4,9,10,18,19). Stewart and Freebaim (17) showed that heat-treated lettuce seed which became insensitive to gibberellic acid germinated well subsequent to treatment with exogenous ethylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the presence cf high levels of ethylene prevents bud growth; the inhibition of internode elongation and leaf expansion play a primary role. Burg and Burg 4 have shown that nodal regions of pea plants produced more ethylene than internodal ones, and that the inhibition of lateral bud break by apical applica.ion of auxin was due to the increased ethylene production associated with the application of high levels of auxin. The extent to which endogenous ethylene production controls bud dormancy remains to be shown.…”
Section: Bud Dormancymentioning
confidence: 99%